Understanding the Motivation behind Students’ Pursuit of Nursing Education - Mey Lona Verawaty Zendrato; Veronika Fernanda Dua Hiko (Archives of Current Research International, 2025)
Nursing students’ motivation before starting their education is very important. Motivation is essential because it affects students’ interest and learning efforts during their education. This study aims to determine global and national phenomena regarding nursing students’ motivation in developing their skills as professional nurses. The method used is a literature review of the Google Scholar, Garuda, PubMed, ScienceDirect database website and the official global and national health database. Journal searches using certain keywords that match the inclusion criteria. Two aspects of motivation were found, namely intrinsic motivation and extrinsic motivation, the dominance of intrinsic motivation creates nursing students with great interest and learning efforts. Extrinsic motivation can present students with achievements when accompanied by support and environmental influence. The quality of future nurses is influenced by nursing education, therefore it is necessary to renew the new student selection system by considering the motivation to choose nursing and the commitment to become a professional nurse. Support, a fun learning system, healthy communication with lecturers can change students’ perspectives on initial motivationvarices grades.